Women's risk-taking behaviour during COVID-19 pandemic: Will work-family enrichment and work satisfaction prevent turnover intention? - I. Gusti Ayu Manuati Dewi; Ismi Rajiani; I Gede Riana; Ni Made Dwi Puspitawati; Muafi; I. Gede Rihayana (Administrative Sciences, 2023)
The COVID-19 pandemic has impacted all employment conditions as working during the pandemic is a risk to employees' health. This study investigates women's intentions to leave their job during times of crisis. However, opportunities for job selection were quite limited, and there are better ways to deal with job insecurity than leaving an organisation. The questionnaires were tested on valid data from 593 female employees of four-star hotels, and structural equation modelling (SEM) was employed. Cultural characteristics and the macroenvironment in Indonesian society cause different practices for women to achieve work-family enrichment, job satisfaction, and turnover intention than in developed Western cultures. Female employees will not be inclined to leave their job even though they are not satisfied. Moreover, work-family enrichment has an essential role in enhancing work satisfaction because it can improve women's quality of life. Work-family enrichment was also found to reduce the intention of women to leave an organisation. However, work-family enrichment has a more substantial influence on intensifying work satisfaction than on deflating the choice to quit during a crisis. Therefore, the research findings revealed that work-family enrichment is essential in improving work satisfaction, increasing employees' likelihood of remaining in the organisation. This study contributes to filling the research gap within work-family enrichment by digging into the practical lessons of women's work behaviour in the service sector, specifically in the hotel industry.
Keywords: 350; hospitality industry; Indonesia; turnover intention; work satisfaction; work-family enrichment